Factors Affecting Non-Performing Loans of Conventional Banking: Evidence in Indonesia Stock Exchange - Hanna Khoirunisa; Cyntia Monalisa Hutauruk; Susy Muchtar (Jurnal Syntax Transformation, 2022)
Majority banks in Indonesia still use loans as the main income to finance their operations. The effects of the NPL will result in dividend payments, high-interest rates and low investment rates resulting in the lower economic development of the country. Based on this, this study was conducted to find out the factors that affect the risk of problematic credit. In this study, the authors used quantitative methods. The independent variables in the study were Return on Assets (ROA), Income Diversification, Bank Capital and Bank Efficiency while the dependent variables were Non-Performing Loans (NPL). The study collected data from 35 banking companies listed on the Indonesia Stock Exchange over 5 years (2016-2020) and used the panel's data regression model for its testing. Findings from this study suggest that Return on Assets (ROA), Bank Capital and Bank Efficiency have a significant negative effect on Non-Performing Loans (NPLs). Income Diversification has no significant effect on non-performing loans (NPLs). The results of this study can be used to present a successful model for banking companies in Indonesia to pay more attention to the mitigation of bad credit risk. All studies have used IBM SPSS 25 as an analysis tool. The conclusions of the results of the study that can be taken are as follows Return on Assets, Bank Capital, and Bank Efficiency have a negative influence on Non-Performing Loans while Income Diversification does not influence Non-Performing Loans